1988
DOI: 10.1016/0378-5955(88)90025-1
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II-induced changes in cochlear blood flow and blood pressure in normotensive and spontaneously hypertensive rats

Abstract: Previous investigations in our laboratory have measured significant increases in the circulating levels of the potent vasoconstrictive hormone, angiotensin II (AII; 26 and 64 pg/100 microliters plasma, normal and noise exposed, respectively), during and following noise exposure in the alert rat (Wright et al., 1981). In the present study, these levels were approximated through intra-arterial infusion in the anesthetized spontaneously hypertensive rat (SHR) and normotensive Wistar-Kyoto (WKY) rat. Laser Doppler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…These findings, the presence of low initial values of perilymphatic oxygenation in sudden deafness [20] and the association of sudden deafness with vascular and hematological disease, including macroglobulinemia, sickle cell disease or polycythemia, suggest a vascular cause for some cases of SHL, such as thrombosis, embolism, vascular spasm or hyperviscosity. Experimental and clinical studies have reported a variation of cochlear blood flow in relation to a variation of arterial pressure, or to sympathetic nerve stimulation, and SHL as a consequence to slow blood flow in the vertebrobasilar system and in the common carotid artery or associated with arterial hypotension [21][22][23][24][25]. Moreover, we have evidenced that an acute hypertension could induce a rapid and reversible decrease in the endochochlear potential in rats, similar to the decreased endocochlear potential observed in anoxic conditions (unpubl.…”
Section: Vascular Hypothesissupporting
confidence: 49%
“…These findings, the presence of low initial values of perilymphatic oxygenation in sudden deafness [20] and the association of sudden deafness with vascular and hematological disease, including macroglobulinemia, sickle cell disease or polycythemia, suggest a vascular cause for some cases of SHL, such as thrombosis, embolism, vascular spasm or hyperviscosity. Experimental and clinical studies have reported a variation of cochlear blood flow in relation to a variation of arterial pressure, or to sympathetic nerve stimulation, and SHL as a consequence to slow blood flow in the vertebrobasilar system and in the common carotid artery or associated with arterial hypotension [21][22][23][24][25]. Moreover, we have evidenced that an acute hypertension could induce a rapid and reversible decrease in the endochochlear potential in rats, similar to the decreased endocochlear potential observed in anoxic conditions (unpubl.…”
Section: Vascular Hypothesissupporting
confidence: 49%
“…T he negative influence of hypertension on the peripheral, cochlear part of the hearing system is well documented [1][2][3][4][5][6][7][8][9]. However, little is known about the central auditory function in patients with hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Autoregulatory capabilities of the cochlear blood fl ow occur through the control of inner ear vasculature [Ren et al, 1994], sympathetic input to the cochlea [Carrasco et al, 1990;Laurikainen et al, 1993;Ren et al, 1993a, b] and the infl uence of various circulating vasoactive hormones and transmitters [Wright et al, 1985;Short et al, 1985;Miller et al, 1986;Sillman et al, 1989;Quirk et al, 1988;Ohlsen et al, 1991]. The aged ear has less capacity to maintain stable blood fl ow and thus may be more vulnerable to stress factors that affect cochlear function [Nakashima et al, 1995;Suzuki et al, 1998], starting with defi cits in OHCs.…”
Section: Teoae and Dpoae Amplitudesmentioning
confidence: 99%